Phytophthora infestans RXLR Effector PexRD2 Interacts with Host MAPKKKε to Suppress Plant Immune Signaling . Issue 3 (14th March 2014) - King, Stuart R.F.; McLellan, Hazel; Boevink, Petra C.; Armstrong, Miles R.; Bukharova, Tatyana; Sukarta, Octavina; Win, Joe; Kamoun, Sophien; Birch, Paul R.J.; Banfield, Mark J.
Abstract : Oomycete pathogens of plants secrete effectors to perturb host cell physiology. This study reveals that the P. infestans RXLR-type effector protein PexRD2 interferes with host MAPKKKε immunity-related signaling to the benefit of the pathogen. Abstract: Mitogen-activated protein kinase cascades are key players in plant immune signaling pathways, transducing the perception of invading pathogens into effective defense responses. Plant pathogenic oomycetes, such as the Irish potato famine pathogen Phytophthora infestans, deliver RXLR effector proteins to plant cells to modulate host immune signaling and promote colonization. Our understanding of the molecular mechanisms by which these effectors act in plant cells is limited. Here, we report that the P. infestans RXLR effector PexRD2 interacts with the kinase domain of MAPKKKε, a positive regulator of cell death associated with plant immunity. Expression of PexRD2 or silencing MAPKKKε in Nicotiana benthamiana enhances susceptibility to P. infestans . We show that PexRD2 perturbs signaling pathways triggered by or dependent on MAPKKKε. By contrast, homologs of PexRD2 from P. infestans had reduced or no interaction with MAPKKKε and did not promote disease susceptibility. Structure-led mutagenesis identified PexRD2 variants that do not interact with MAPKKKε and fail to support enhanced pathogen growth or perturb MAPKKKε signaling pathways. Our findings provide evidence that P. infestans RXLR effector PexRD2 has evolved to interact with a specific host MAPKKK to perturb plant immunity–related signaling.